Kajian Diftong Dan Gugus Konsonan Pada Bacaan Anak Mengarungi Samudera Kehidupan Karya Muh. Sunardiyanto. - Melsa Nuraisyah; Selfi Novita Mariam; Welly Karmelia (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Analyzing the study of diphthongs and consonant clusters in the children's reading book" wading the ocean of life " by Muh.Sunardiyantothis research uses the literature study method. Stages in the analysis of data in the form of stages of data collection, data analysis and writing stages. In this study the researchers analyzed the use of diphthongs ai, au, oi and consonant clusters studies show that the diphthong /ai/ is used 79 times in the children's reading book "wading the ocean of life", kh, ng, ny, sy, nk in children's reading across the ocean of life.In addition to the consonant cluster /ny/ quite a lot found but not more than consonant cluster /ng/, 146 is the result of analysis of the consonant cluster /ny/ along with the page was already recorded in the results. The existence of diphthongs in children's reading” wading the ocean of life " by Muh. Sunardiyanto, there are only a few /ai /and/ au /while/ ei /and/ oi /are not found as well as consonant clusters/ nk/, in consonant clusters only found/ ng/,/ kh/,/ ny/, and/sy/. Based on the results and discussion of this article, it informs what diphthongs and consonant clusters are and on which pages the diphthongs and consonant clusters are located.